Pembinaan Ekstrakurikuler Tahfidz Qur’an dalam Meningkatkan Motivasi Mengahafal Al-Qur’an di SMA Negeri 1 Percut Sei Tuan - Neliwati; Jamilah; Miftahul Jannah Ira; Rini Nurwana Saragih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
his research aims to find out how the coaching carried out in extracurricular tahfidz Qur'an increases motivation to memorize the Qur'an at SMA N 1 Percut Sei Tuan. The method in this research uses qualitative methods through a field approach. Researchers carry out research by describing facts that occur naturally by describing all activities carried out through a field approach, where intensive data and information collection efforts are accompanied by analysis and re-testing of everything that has been collected. The results of this research show that the extracurricular coaching of tahfidz Qur'an is carried out by the Mentors and Coaches in the extracurricular. The role played is in the form of providing motivation, gifts and praise.